Woman Violence in Afghanistan and The Return of Taliban in Contagious Violence Perspektive - Valentia Nadya Dasadwiastaning (Jurnal Syntax Transformation, 2023)
This research shows that contagious violence is playing important role in spreading violence against women in Afghanistan. This research argues that it is important to pay attention on how violence expose a subject, when it happened and who ie exposed by violence at that time. It is important also to produce immunity amidst society in Afghanistan. It is important to prevent wider transmission of violence in Afghanistan. Contagious violence and immunity theory shows that Taliban is the Host of violence that needs to overcome. Taliban massively spreading violence to disrupt immune system of anti violence in Afghanistan. Hiding the prove and preventing report activity will causes horrible silent spreading of violence. This research also shows that tracing and immediate response to any violence act is needed to cut off chain of contagious violence. Finding violence cluster and directly intervene is needed to prevent the subject who already exposed becoming more violent than perpetrator. Produce immunity system and direct intervention into all cluster of violence amidst society is more effective than urging Taliban to stop violence itself.